One Person Company in India: A Critical Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The concept of a One Person Company (OPC) represents one of the most transformative reforms in post-independence Indian corporate law. Introduced under Section 2(62) of the Companies Act, 2013, and operationalized through the Companies (Incorporation) Rules, 2014, the OPC enables a single natural person to incorporate, own, and manage a private limited company with full limited liability protection. This paper critically examines the historical origins, statutory framework, comparative global dimensions, jurisprudential underpinnings, advantages, and limitations of the OPC model in India. Particular attention is given to landmark case law including Salomon v A Salomon & Co Ltd AC 22, Lee v Lee’s Air Farming Ltd AC 12, and Macaura v Northern Assurance Co Ltd AC 619 that together form the doctrinal foundation upon which the OPC concept rests. The paper concludes that while the OPC is a commendable legislative innovation, several structural deficiencies including tax neutrality, compliance burden, conversion rigidity, and misuse potential render it an incomplete solution for India’s vast community of small and micro entrepreneurs.